Pengaruh Profitabilitas, Likuiditas, Dan Ukuran Perusahaan Terhadap Struktur Modal - Ivandi Taslim, Liana Susanto (Fakultas Ekonomi, Universitas Tarumanagara, 2021)
The purpose of this research is to obtain empirical evidence about the effect of profitability, liquidity, and firm size on capital structure of property & real estate companies listed on the Indonesian Stock Exchange for the period of 2016-2018. This research used 35 samples of property & real estate companies that have been selected previously using purposive sampling method for three years. This research data was processed using IBM SPSS 25. The result of this research shows that liquidity has a significant negative effect on capital structure and firm size has a significant positive effect on capital structure, while profitability does not has no effect on capital structure.